Pushing the limits of quantifying complexity - Ho, Matthew Shu Hui (2017)
In this article, we study the complexity of a process through the use of the classical epsilon machine. Then, we shift into the quantum regime to study the analogous counterpart of the classical epsilon machine, known better as the quantum epsilon machine. We will look into the quantum epsilon machine’s behaviour, and introduce a method of reducing the complexity to its limits. We also seek to understand how changing the measurement basis affects the quantum epsilon machine.